Documentation of the nopoh ritual by the Che Wong in Kampung Senil, Krau Pahang: flower season / Fatin Nazihah Rosli - Rosli, Fatin Nazihah (2020)
Che Wong is one out of eighteen Orang Asli tribes located in Pahang. Singing séance is one of the traditional cultural rituals performed by the Che Wong, known as ‘nopoh’ in Che Wong language. It has been practised in the Che Wong community for centuries. However, they seem to have little knowledge of their traditional culture practice since modernization that has happened in Kuala Gandah taken over the Che Wong traditional lifestyle especially among the young generation. Observation of the cultural practices and lifestyle shows that only some of the Che Wong elders still possess traditional cultural knowledge and few are still practising the rituals. Such knowledge will be lost completely if no action is taken by the community to preserve the knowledge, traditions and culture. This study explores the ritual practised during the flowering season, known as ‘nopoh bukau’ by the Che Wong in Kampung Senil living deep in the forest of Krau, Pahang. Fulfilling the objectives of this study, data was collected through observation and examinations of the documented visuals on the ‘nopoh bukau’ ritual. The findings from the analysis of the data revealed that when the Che Wong performed the traditional ritual practice, indirectly, they were preserving the environment and living a balanced life, in harmony with nature and supernatural beings. The stories in their songs were representations of their beliefs and identity. These findings draw attention to the significance of the ritual and the need to preserve the traditional cultural practices for future generations.